Community Empowerment in Sajang Village Through Coffee Soap Making and Entrepreneurship Training - Zulys, Agustino; Syauqi, Muhammad Iqbal; Adriana, Elva Dissa; Istiqomah, Muhsinatul; Susanto, Bambang Heru; Haidir, Banu Muhammad (ASEAN Journal of Community Engagement, 2023)
Rural entrepreneurship is believed to be one of the most strategic ways to advance community empowerment that can directly lead to national economic development, by optimizing local resources, technology, and digitalization. This article elaborates on the program conducted to support the community’s economy and increase business and digital marketing literacy in Sajang Village, Sembalun, East Lombok. The program consists of bar soap products making workshop that optimizes coffee and copra as the local potential, targeted for people of productive age who are interested in establishing a home-based business. The soap manufacturing process is informed by laboratory research formulas that have been tested and are safe, and the produced soap offers advantages over ordinary soap for both aromatherapy and skin care capacities to overcome acne and remove dead skin cells. The program’s objective is to stimulate the growth of local entrepreneurship and advance the development of authentic regional products as a sustainable income source that will strengthen the local economy. The analysis of the program’s pre- and post-tests and questionnaires indicates that such programs have enhanced participants’ literacy, skills, and motivation. A small business group was founded in subsequent to the program to launch the business; however, additional support from the local government and company is still required to maintain a supportive atmosphere for new entrepreneurs. Such entrepreneurship training could be an effective way to empower a community and open further opportunities for people in other rural areas.